Fostering creativity in the elementary music classroom through actively creating and performing - Anschutz, Kristin (Kansas State University, 2022)
The activities created for this lesson plan were designed to allow students the opportunity to create as a small group and have that creation fit into a larger ensemble for performance. Students were allowed to select one of four modes for creation: instrumental accompaniment, movement, singing, or body percussion ostinato. Their compositions were based around a section of poetry that then tied back into a full Orff ensemble using rondo form. The two areas in my teaching where I see the most room for development as a result of my graduate studies are active music making and creativity. As a Kodaly-inspired teacher, my classroom is full of opportunities for students to joyfully experience music by singing, dancing, and playing games. However, my experiences at graduate school and through teaching during the pandemic have challenged me to incorporate more instrumental music opportunities using Orff instruments and ukuleles. I have been working to hone my skills at providing the students a music-making experience in each class where they leave feeling excited at performing a piece of music together, be that instrumental or vocal. Continuing to foster creativity in my classroom is another area of development. My studies have convinced me of the need to let students more freely explore compositional opportunities without too many rules and prompts as a means of developing the students’ own areas of musical interest. In this area I feel I am often limited by my own desire to control their creations as well as the logistics of creating a safe, structured learning environment. As the students become more comfortable exploring and creating in a setting with few limiting parameters, I anticipate being able to add specific rules back into the process to allow them to record or notate their creations in order to share them with others. This set of lessons allowed me the opportunity to work on efficiently teaching parts for an Orff ensemble and on structuring varied creative tasks for student success in developing the rondo. Both of these are skills I hope to build on as I plan other, similar activities in the coming school year and continue to build a sequence for fostering creativity in my classroom.
Keywords: Elementary music; Creativity; Orff; Composition